2012
DOI: 10.2172/1056493
|View full text |Cite
|
Sign up to set email alerts
|

Lithium As Plasma Facing Component for Magnetic Fusion Research

Abstract: The use of lithium in magnetic fusion confinement experiments started in the 1990's in order to improve tokamak plasma performance as a low-recycling plasma-facing component (PFC). Lithium is the lightest alkali metal and it is highly chemically reactive with relevant ion species in fusion plasmas including hydrogen, deuterium, tritium, carbon, and oxygen. Because of the reactive properties, lithium can provide strong pumping for those ions. It was indeed a spectacular success in TFTR where a very small amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…It has been found that the energy confinement duration of the discharge in [22,23] a keV temperature plasma edge was significantly enhanced by the pulses that were preceded by lithium pellet injections [22,24]. In addition, lithium has become increasingly recognized as a potential solution to combating divertor heat flux issues within fusion reactors, as ionized lithium atoms form highly radiative plasma layers which could significantly decrease heat flow into divertors surfaces [25][26][27][28][29][30]. As it happens, evaporated lithium in its ionic form (partially stripped ions) combined with hydrogen, carbon, and oxygen atoms increased the possibility for inelastic collisions between multiply charged ions and neutral atoms -stimulating inelastic collision research not only out of general scientific curiosity but also as essential tools in fusion-related research [5].…”
Section: Lithium (Li 2+ ) -Hydrogen (H) Collision Cross Sectionsmentioning
confidence: 99%
“…It has been found that the energy confinement duration of the discharge in [22,23] a keV temperature plasma edge was significantly enhanced by the pulses that were preceded by lithium pellet injections [22,24]. In addition, lithium has become increasingly recognized as a potential solution to combating divertor heat flux issues within fusion reactors, as ionized lithium atoms form highly radiative plasma layers which could significantly decrease heat flow into divertors surfaces [25][26][27][28][29][30]. As it happens, evaporated lithium in its ionic form (partially stripped ions) combined with hydrogen, carbon, and oxygen atoms increased the possibility for inelastic collisions between multiply charged ions and neutral atoms -stimulating inelastic collision research not only out of general scientific curiosity but also as essential tools in fusion-related research [5].…”
Section: Lithium (Li 2+ ) -Hydrogen (H) Collision Cross Sectionsmentioning
confidence: 99%
“…This approach is difficult for the person with Asperger's syndrome because of the bad social interpretations and a maturity that is not consistent with his age. Masayuki, (2012) The lack of preparation and experience in terms of social interactions leads to these children or adults to a situation of failure. Adequate support, before or during schooling, would therefore allow them to experience fewer difficulties.…”
Section: Incidence Of Different Disordersmentioning
confidence: 99%
“…Thermonuclear fusion stands out among other concepts due to the large energy/volume ratio of its fuels and to the natural abundance of the deuterium isotope (D or 2 H), which can be found naturally on sea-water and corresponds to one on every 6700 atoms of Hydrogen [Freidberg (2007)]. On the other hand, tritium (T or 3 H), is quite scarce in nature, but the neutron released by the D-T reaction can be used to produce more tritium, in situ, by means of its reaction with lithium (Li), also abundant in nature [Freidberg (2007); Mazayuki (2012)].…”
Section: Introductionmentioning
confidence: 99%